Trends for Stirling Engines in Households: A Systematic Literature Review - Anna Kubule; Jānis Kramens; Madara Bimbere; Nerijus Pedišius; Dagnija Blumberga (Energies, 2024)
Reliable heat and power supply are among the basic household needs nowadays. It is especially topical in rural or distant locations that may be cut off from the energy grid due to extreme weather or other events. Nonetheless, the sustainability of our power production systems has to be considered to sustain our planet’s long-term abilities to provide energy resources and a viable environment. Renewable energy resources must be prioritized in rural and remote areas, simultaneously strengthening distributed production ability and self-sufficiency. In this context, the use of the Stirling engine for heat to power generation in households, on the scale of small communities, and by using only renewable resources is becoming increasingly topical. Therefore, this research aims to identify the current state-of-the-art for Stirling engine applications using biomass as a renewable energy source, in the context of sustainability and energy security. The paper summarizes the current research tendencies at the household level in the use of biomass-based Stirling engines for renewable heat and power generation in decentralized energy systems. The methodology applied is a structured literature review and content analysis. The research results corroborate the progress towards the use of renewable resources and towards increased energy efficiency because the keyword and overlay analysis showed more frequent publishing in these areas. The content analysis on two more specific sub-directions of interest, i.e., biomass-fuelled Stirling engine use in households and Stirling engine implications on energy security, showed that though research activity in these directions has increased lately, more profound research is needed, especially on aspects of energy security and independence. The content analysis revealed a lack of in-depth analysis on the effects of Stirling engine use on energy security or energy independence, which is suggested as a topical subject for future research.